Natural incidence of tremorgenic mycotoxins in bakery products - and S.M. REDDY, MD. RAFIUDDIN, S. GIRISHAM (Indian Phytopathology, 2002)
Different bakeries in Andhra Pradesh, India, were surveyed for the incidence of moulds and mycotoxin contamination, during 1995-96. Only species of Aspergillus and Penicillium were detected in bakery products, as well as a variety of mycotoxins including tremorgens such as tryptoquivaline, verruculogen, paxilline, aflatrem and penitrems. In some of the samples aflatoxins were also detected. Foods which were not properly stored or over-stored showed visible growth of moulds.